Spatial spillovers and innovation activity in European regions - Rosina Moreno; Raffaele Paci; Stefano Usai (European Regional Science Association (ERSA), 2004)
This paper explores the spatial distribution of innovative activity and the role of technological spillovers in the process of knowledge creation across 138 regions of 17 countries in Europe (the 15 members of the European Union plus Switzerland and Norway). The analysis is based on an original statistical databank set up by CRENoS on regional patenting at the European Patent Office spanning from 1978 to 1997 and classified by ISIC sectors (3 digit). In a first step, a deep exploratory spatial data analysis of the dissemination of innovative activity in Europe is performed. Some global and local indicators for spatial association are presented, summarising the presence of a dependence process in the distribution of innovative activity for different periods and sectors. Secondly, we attempt to model the behaviour of innovative activity at the regional level on the basis of a knowledge production function. Econometric results points to the relevance of internal factors (R&D expenditure, economic performance, agglomeration economies). Moreover, the production of knowledge by European regions seems to be also affected by spatial spillovers due to innovative activity performed in other regions. Keywords: Innovative activity, Spatial analysis, European regions, Knowledge production function.
Keywords: 330; Innovative activity; Spatial analysis; European regions; Knowledge production function